LINGUOCULTURAL STUDY OF PHRASEOLOGICAL UNITS - Mamatov, Abdugafur (Журнал иностранных языков и лингвистики, 2021)
This article is devoted to the study of phraseological units on the basis of linguoculturological, the relationship of language and culture, the specificity of the national mentality.